2020
DOI: 10.1111/jir.12782
|View full text |Cite
|
Sign up to set email alerts
|

Participation in sport and physical activity in adults with intellectual disabilities

Abstract: Background People with intellectual disability face a number of barriers to participation in physical activity. This paper aimed to determine rates of sport and physical activity participation in an Australian sample of adults with intellectual disability, compared with rates of participation in the general Australian population. A secondary aim was to investigate factors that may contribute to participation of adults with intellectual disability. Method Participants were part of the Australian Child to Adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
1
27
0
2
Order By: Relevance
“…No significant association was reported with body fat in either children or adults with PWS [ 7 , 10 , 31 , 32 ]. Reported participation in sports and PA was not found to be associated with physical function in children with PWS [ 28 ] but a trend towards an association between daily steps and walking capacity ( p = 0.13) was reported in adults with PWS [ 10 ]. Finally, in children with PWS, no significant association was found between habitual PA and a composite score of metabolic syndrome [ 7 ], markers of inflammation [ 7 ], behavior and emotional problems [ 28 ], or the degree of intellectual disability [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant association was reported with body fat in either children or adults with PWS [ 7 , 10 , 31 , 32 ]. Reported participation in sports and PA was not found to be associated with physical function in children with PWS [ 28 ] but a trend towards an association between daily steps and walking capacity ( p = 0.13) was reported in adults with PWS [ 10 ]. Finally, in children with PWS, no significant association was found between habitual PA and a composite score of metabolic syndrome [ 7 ], markers of inflammation [ 7 ], behavior and emotional problems [ 28 ], or the degree of intellectual disability [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review described the level of habitual PA and sedentary behavior in children and adults with PWS. Findings from 14 studies were synthetized, of which 12 studies provided an objective measure of PA or PA-related energy expenditure using accelerometers [ 6 , 7 , 8 , 9 , 10 , 11 , 26 , 31 ], pedometers [ 20 , 22 ], or indirect calorimetry measures in a metabolic chamber [ 29 , 32 ], and two studies provided a self-reported measure of PA [ 28 , 30 ]. The total volume of PA was consistently found to be lower in patients with PWS compared to patients with non-syndromic obesity [ 8 , 26 , 29 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with regard to the relationship between age and time spent exercising, we found that as subjects with IDs age, they dedicate more time to participating in cooperative physical activities. This could be the result of the well-being that physical activity provides, the benefits that exercise can lead to, a greater awareness of the importance of exercise for one's health, or because it is an important source of social interaction [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with DS have lower aerobic capacity, lower peak heart rates, and lower levels of isokinetic muscular strength [2]. Various scholars recommend health maintenance through regular physical activity for adults with DS [3]. The positive relationship between physical fitness and health is well studied [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sedentary lifestyle of this population is often associated with obesity and low levels of physical fitness. Although opportunities to participate and compete in sports are available through the Special Olympics and other organizations, for example, not everyone with ID participates in organized sports activities [3,12]. For these reasons, we believe that presenting objective data will encourage the guardians of this population to enroll people with DS to practice and participate in sports.…”
Section: Introductionmentioning
confidence: 99%